The official history of the Joint Intelligence Committee - Goodman, Michael S. (New York Routledge, 2016)
"This first volume of the Official History of the Joint Intelligence Committee draws upon a range of released and classified papers to produce the first, authoritative account of the way in which intelligence has been used to inform UK foreign policy. For more than half a century, the Joint Intelligence Committee (JIC) has been a central player in the secret machinery of the British Government, acting as broker between the intelligence agencies and the policy-makers. Since its creation, the JIC has been involved in almost every key foreign policy decision taken by the British Government. This volume covers the evolution of the JIC in 1936 and culminates with its role in the fateful events of Suez in 1956. Throughout this period the JIC was a sub-committee of the Chiefs of Staff, and this book charts its vital input into key foreign and defence policy decisions and British responses to global developments. This book will be of much interest to students of intelligence studies, British politics, international diplomacy, security studies and International Relations in general. Michael S. Goodman is Reader in Intelligence and International Affairs in the Department of War Studies, King's College London. He is author or editor of four previous books, including the Routledge Companion to Intelligence Studies (2013)"--
v. 1. From the approach of the Second World War to the Suez Crisis
Includes bibliographical references (v. 1, p. [450]-463) and index.
Keywords: Great Britain. -- Joint Intelligence Committee -- History; Intelligence service -- Great Britain -- History -- 20th century; HISTORY / Europe / Great Britain; POLITICAL SCIENCE / Political Freedom & Security / Intelligence; POLITICAL SCIENCE / Political Freedom & Security / International Security; Great Britain -- Foreign relations -- 20th century